Relationship between gut microbiome and allergic asthma - Ryoji Hirota (Global Journal of Allergy - Peertechz Publications, 2022)
Since the late 20th century, environmental exposure to endotoxins has been very low and type I allergic disease has increased. In addition, we have increased exposure to PM2.5 and other chemicals. Recently, there is concern that the daily use of hygiene products containing antimicrobial substances is associated with an increased prevalence of allergies. It has been noted that these antimicrobial substances may exacerbate allergies. In our study, we confirmed that intratracheal administration of aqueous mite solution as an inhaled antigen and antimicrobial substance as an aggravating chemical induced much stronger allergic bronchial asthma in mice than in mice that received intratracheal mite solution alone. Thus, allergies have been found to be exacerbated by simultaneous exposure to both environmental antigens and man-made chemicals (adjuvants). Next, we analyzed 16S rRNA of the gut microbiota of triclosan-treated mice that developed an allergy. The bacterial gene abundance of 16S rRNA of Deltaproteobacteria, Erysipelotrichi and Clostridia was increased in a dose-dependent manner in triclosan-treated mice, while Bacteroides were decreased in these mice. The composition of the gut microbiota was altered after triclosan treatment and correlated with the exacerbation of asthmatic disease in these mice.  In conclusion, because triclosan exacerbated the condition of allergic asthma in mice that inhaled mite antigens and were given triclosan to drink, and this condition was associated with an increase or decrease in certain bacteria in the gut, we suspect that if allergy sufferers continue to use triclosan, they will inhale dust mites and house dust on a daily basis, which may aggravate their allergy symptoms. Overall, the overuse of antimicrobials and preservatives in current daily life risks further increasing the number of allergic patients. The authors believe that it is time to rethink this lifestyle.